A framework for analysis of the supplier selection in green supply chain - Tundys, Blanka; Rzeczycki, Andrzej; Fernando, Yudi (Inderscience Enterprises Ltd., 2019)
The main purpose of the article is to build the framework of the supplier assessment model in the green supply chain. To achieve this purpose, specific objectives were taken to consideration: 1) an indication of the basis for the analysis of supplier selection in green supply chain; 2) identify of the gaps that exist in this respect, in the literature; 3) the identification of the criteria catalogue for the supplier selection with the particular emphasis on the needs of green supply chain; 4) develop a model to assess the green supply chain, taking into account the sustainable aspects; 5) using AHP method to the investigation and analysis of the meaning of the selected criteria, on the example of companies operating in the Polish economy; 6) indication which of them are the most important and which of them did not play an important role in the selection process of the suppliers.